Differences and Similarities in the Pattern of Early Metabolic and Morphologic Response after Induction Chemo-Immunotherapy versus Induction Chemotherapy Alone in Locally Advanced Squamous Cell Head and Neck Cancer - Beck, Michael; Semrau, Sabine; Haderlein, Marlen; Gostian, Antoniu-Oreste; Hartwich, Julius; Müller, Sarina Katrin; Kallies, Annett; Geppert, Carol-Immanuel; Schonath, Miriam; Putz, Florian; Gaipl, Udo; Frey, Benjamin; et al. (Cancers, 2022)
Simple Summary There are differences and similarities when assessing the short-term therapeutic response of chemotherapy and chemotherapy plus immunotherapy using imaging techniques, which may be necessary to make treatment decisions in malignant head and neck tumors. After both chemo- and immunochemotherapy, remission becomes measurable in cross-sectional and metabolic diagnostics after only one cycle of therapy, with (18)FDG-PET/CT predicting complete remission of tumor cells in a representative biopsy better than MRI/CT examination in both therapeutic modalities. While complete tumor remission is highly likely (88%) after immunochemotherapy in tumors with low residual activity (<= 40% of initial SUV), this is less common after chemotherapy alone (65%). In metabolic nonresponse with more than 80% residual activity, the probability of complete remission nevertheless is low after chemotherapy alone (6%). After immunochemotherapy, these false nonresponders are common (35%), requiring additional diagnostics by deep biopsy. Cases of pseudoprogression with an increase of SUVmax of more than 125% of the baseline were not observed. Background: In head and neck cancer patients, parameters of metabolic and morphologic response of the tumor to single-cycle induction chemotherapy (IC) with docetaxel, cis- or carboplatin are used to decide the further course of treatment. This study investigated the effect of adding a double immune checkpoint blockade (DICB) of tremelimumab and durvalumab to IC on imaging parameters and their significance with regard to tumor cell remission. Methods: Response variables of 53 patients treated with IC+DICB (ICIT) were compared with those of 104 who received IC alone. Three weeks after one cycle, pathologic and, in some cases, clinical and endoscopic primary tumor responses were evaluated and correlated with a change in 18F-FDG PET and CT/MRI-based maximum-standardized uptake values (SUVmax) before (SUV(max)pre), after treatment (SUV(max)post) and residually (resSUV(max) in % of SUV(max)pre), and in maximum tumor diameter (D-max) before (D(max)pre) and after treatment (D(max)post) and residually (resD). Results: Reduction of SUVmax and D-max occurred in both groups; values were SUV(max)pre: 14.4, SUV(max)post: 6.6, D(max)pre: 30 mm and D(max)post: 23 mm for ICIT versus SUV(max)pre: 16.5, SUV(max)post: 6.4, D(max)pre: 21 mm, and D(max)post: 16 mm for IC alone (all p < 0.05). ResSUV(max) was the best predictor of complete response (IC: AUC: 0.77; ICIT: AUC: 0.76). Metabolic responders with resSUV(max) <= 40% tended to have a higher rate of CR to ICIT (88%; n = 15/17) than to IC (65%; n = 30/46; p = 0.11). Of the metabolic nonresponders (resSUV(max) > 80%), 33% (n = 5/15) achieved a clinical CR to ICIT versus 6% (n = 1/15) to IC (p = 0.01). Conclusions: ICIT and IC quickly induce a response and 18F-FDG PET is the more accurate modality for identifying complete remission. The rate of discrepant response, i.e., pCR with metabolic nonresponse after ICIT was >30%.
CRIS-Team WoS Importer:2022-10-21